Benefit and risk of early intravenous heparin after thrombolysis in patients with acute ischemic stroke - Xu Tong; Yibin Cao; Wenzhi Wang; David Wang; Yongjun Wang; Yilong Wang; the Thrombolysis Implementation, Monitor of Acute Ischemic Stroke in China (TIMS‐China) Investigators (Brain and Behavior, 2020)
Abstract Background and purpose We performed a retrospective analysis of the “Thrombolysis Implementation and Monitor of Acute Ischemic Stroke in China (TIMS‐China)” registry to explore the benefit and risk of intravenous thrombolysis (IVT) followed by intravenous heparin (IVH) in acute ischemic stroke (AIS) patients. Methods In the TIMS‐China database, the patients who received IVH immediately after IVT (Early IVH group) and those who initiated antithrombotic therapy (ATT) until 24 hr after IVT (Standard ATT group) were screened for this comparison. Propensity score (PS) matching was performed between both groups. The logistic regression analysis was performed in the matched population to compare all the efficacy and safety outcomes. Results Of 1,437 patients in this study, 119 received early IVH and 1,318 cases initiated standard ATT. After PS matching (1:2), 117 pairs were identified. The early IVH group had higher proportions of neurological improvement at 24 hr (OR = 2.24, 95% CI = 1.42–3.53) and 7 days (OR = 1.92, 95% CI = 1.22–3.03), better chance of excellent recovery (OR = 1.69, 95% CI = 1.07–2.67) and functional independence (OR = 1.77, 95% CI = 1.13–2.78) at 90 days, and a lower 90‐day mortality (OR = 0.44, 95% CI = 0.21–0.92) than standard ATT group. Additionally, early IVH did not increase the risk of symptomatic intracranial hemorrhage (OR = 0.92, 95% CI = 0.34–2.48). Conclusions IVH immediately after thrombolysis seems to be safe and potentially more effective as compared with standard ATT delay of 24 hr for a subset of AIS patients.